CONCORDANCE BETWEEN THE BLOOD PRESSURE PROFILE (BPP) AND AMBULATORY BLOOD PRESSURE MONITORING (ABPM) FOR THE DIAGNOSIS OF HIGH BLOOD PRESSURE (HBP) IN PRIMARY HEALTH CARE. (June 2018) - Herrera, E. Lorca; Michea, L.; Toro, L.; Alban, N.; Contreras, D.; Paccot, M.; Escobar, M.
Abstract : Objective: : The general aim of the Global Project of Standardized Treatment of Hypertension is to evaluate the standardized strategy for diagnosis and control of hypertension, including the use of ABPM for confirmation hypertension diagnosis and follow-up treatment. The objective of the present study is to evaluate the concordance in the diagnosis of hypertension conducted with BPP and ABPM. Design and method: In a pilot phase, the project was implemented in 3 family health centers at Santiago (Metropolitan Health Service South East –SSMSO-). Subjects aged 15 to 79 years with suspicion of HBP, who were given BP measurements via BPP, 3 serial blood pressure measurements under standardized conditions (7–15 days) with automatic monitor (Omron HEM 907 ®), and 24-hour ABPM (Mobil-O-Graph ® equipment), according to current guidelines. Correlation between continuous variables (SBP and DBP, between BPP and ABPM average/day/night) was determined. Concordance was assessed in the diagnosis of HBP between BPP and ABPM, by determination of Kappa coefficient. The study was approved by the SSMSO Ethics Committee and informed consent was obtained from all participants. Results: : 123 subjects were recruited (50% of total calculated sample); Age: 53 ± 15 years; Male Sex: 66 (53, 2%); BMI: 29 ± 5 kg/m2; Average BP per BPP: 1st measurement: SBP: 139 ± 10 mmhg/DBP: 84 ± 9 mmhg. Patients with HBP according to BPP: 103 (83%); Stage 1:87 (69%); Stage 2:16 (14%). The analysis of correlation between BPP and ABPM showed a low correlation with SBP (R2 BPP vs ABPM: min: 0.14; max: 0.18) and moderate with DBP (R2 BPP vs ABPM: min: 0.21; max: 0.41). We observed low concordance in the diagnosis of HBP between BPP and ABPM, being greater for night ABPM (Kappa coefficient vs ABPM average: 0.18; vs ABPM Day: 0.17; vs ABPM Night: 0.30). Conclusions: : The results show high discordance between BPP and ABPM in the diagnosis of hypertension. If technical superiority of the ABPM is accepted, the BPP diagnosis would have a high rate of false positives. It is still pending to determine whether these results are confirmed by completing the total sample size.